A new nonlinear iterative method for SPN theory. (December 2017) - Pan, Qingquan; Lu, Haoliang; Li, Dongsheng; Wang, Kan
Abstract: The SPN theory shows a great potential for solving the neutron transport equation in the Next Generation Reactor Physics Calculation. However, the numerical instability problem will be encountered in some cases when solving the SPN equation with the conventional nonlinear iterative method. In order to solve the problem, a new coupling corrective relationship which focuses on the angular coupling is put forward, and the new nonlinear iterative method has more margin to adjust the coupling corrective coefficients with that new relationship. As an example, the code named NLSP3 for solving the SP3 equation with the new nonlinear iterative method is developed, and the numerical results demonstrate the feasibility of the new method.